2021
DOI: 10.3390/ijms22052301
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biomarkers and Regenerative Medicine for Diabetic Neuropathy

Abstract: Diabetic neuropathy is one of the most common complications of diabetes. This complication is peripheral neuropathy with predominant sensory impairment, and its symptoms begin with hyperesthesia and pain and gradually become hypoesthesia with the loss of nerve fibers. In some cases, lower limb amputation occurs when hypoalgesia makes it impossible to be aware of trauma or mechanical stimuli. On the other hand, up to 50% of these complications are asymptomatic and tend to delay early detection. Therefore, sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 81 publications
0
13
0
1
Order By: Relevance
“…Blood biomarkers in diabetes have concentrated on the most common subtype of diabetic peripheral neuropathy, distal painful sensory neuropathy in patients with type 2 diabetes. Much of the work has concentrated on metabolic biomarkers and neurotrophic factors, given their role in nerve regeneration and repair 24 …”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Blood biomarkers in diabetes have concentrated on the most common subtype of diabetic peripheral neuropathy, distal painful sensory neuropathy in patients with type 2 diabetes. Much of the work has concentrated on metabolic biomarkers and neurotrophic factors, given their role in nerve regeneration and repair 24 …”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…There have been a multitude of large case–control studies of patients with type 2 diabetes, with and without neuropathy, in which inflammatory and metabolic markers have been measured using cytokine and apocrine arrays 24 . These studies have consistently shown an increase in a number of inflammatory markers in type 2 diabetic patients with neuropathy compared to those without neuropathy; these include TLR 4, TNF alpha, TGF beta, CXCL10, MCP‐1, adhesion molecule E‐selectin and interleukins including IL‐6 IL‐1, IL12p70, IL‐13 and IL‐17A 25–29 .…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…In the developmental stage, it changes from alpha enolase form to gamma enolase in neural tissue. NSE is a potential hall-marker in diabetic complications including diabetic peripheral neuropathy and DR [60,61]. A clinical study revealed that an elevated level of NSE in serum was found in diabetes mellitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…The primary symptoms of DPN are paresthesia and neuropathic pain in the lower limbs [ 5 , 6 ]. However, almost half of patients present asymptomatically in the early phases of DPN [ 7 ], which may result in delayed diagnosis and a high rehospitalization rate. Therefore, timely diagnosis and treatment are essential for preventing the progression and complications of DPN.…”
Section: Introductionmentioning
confidence: 99%